2019
DOI: 10.1016/j.jgr.2018.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Korean Red Ginseng (Panax ginseng Meyer) with enriched Rg3 ameliorates chronic intermittent heat stress–induced testicular damage in rats via multifunctional approach

Abstract: BackgroundPanax ginseng Meyer, known as Korean Red Ginseng (KRG), is one of the important age-old traditional herbs used in boosting libido and improving male fertility. In this study, the effects of Rg3-enriched KRG extract (KGC04P) on heat stress–induced testicular damage in experimental rats was evaluated.MethodsMale rats (Sprague-Dawley) were divided into four groups (n = 10): normal control (NC), heat-stressed control (HC), heat-stressed plus KGC04P-100 mg/kg (HK100), and heat-stressed plus KGC04P-200 mg/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 46 publications
4
12
0
Order By: Relevance
“…Ginsenosides are abundant in ginseng stems and leaves (GSLS), belong to nontraditional medicine parts, but are considered the most important medicinal resources (Wang, Yang, Yu, Yao, & Ren, 2013; Zhuo et al, 2017). Prior to the present study, Kopalli et al (Kopalli et al, 2019) have confirmed that KRG extract (enriched ginsenoside Rg3) protects the scrotal from chronic intermittent HS‐induced spermatogenic damage and help to recover testicular function by restoring intrinsic anti‐oxidant defenses. Recent research suggests that HS‐induced testicular damage may be related to apoptosis, oxidative stress, and autophagy (Li, Li, Zhou, Dai, & Li, 2018; Park et al, 2017).…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…Ginsenosides are abundant in ginseng stems and leaves (GSLS), belong to nontraditional medicine parts, but are considered the most important medicinal resources (Wang, Yang, Yu, Yao, & Ren, 2013; Zhuo et al, 2017). Prior to the present study, Kopalli et al (Kopalli et al, 2019) have confirmed that KRG extract (enriched ginsenoside Rg3) protects the scrotal from chronic intermittent HS‐induced spermatogenic damage and help to recover testicular function by restoring intrinsic anti‐oxidant defenses. Recent research suggests that HS‐induced testicular damage may be related to apoptosis, oxidative stress, and autophagy (Li, Li, Zhou, Dai, & Li, 2018; Park et al, 2017).…”
Section: Discussionsupporting
confidence: 74%
“…Prior to the present study, Kopalli et al (Kopalli et al, 2019) have confirmed that KRG extract (enriched ginsenoside Rg3) protects the scrotal from chronic intermittent HS-induced spermatogenic damage and help to recover testicular function by restoring intrinsic anti-oxidant defenses. Recent research suggests that HS-induced testicular damage may be related to apoptosis, oxidative stress, and autophagy (Li, Li, Zhou, Dai, & Li, 2018;Park et al, 2017).…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Moreover, Rg3 could reverse TP-induced apoptosis in MLTC-1 cells via downregulating the levels of Bax, active caspase 3, Cyto c and active caspase 9, and upregulating the level of Bcl-2. Kopalli et al indicated that Rg3 could alleviate hyperthermia-mediated male infertility 38. Ginseng could protect fertility factors and testicular damage in immobilization stress-induced rats 39.…”
Section: Discussionmentioning
confidence: 99%
“…Over the past decades, HS research has been carried out in many species, such as humans [ 11 ], cattle [ 12 ], pigs [ 13 , 14 ], corals [ 15 ], and rats [ 16 , 17 ]. However, the regulatory mechanisms of HS are still unclear.…”
Section: Introductionmentioning
confidence: 99%